Parate Eksekusi Oleh Kreditur Kepada Debitur Atas Objek Jaminan Kredit Akibat Wanprestasi - Apituley, Werner Marfendo; Saija, Ronald (KANJOLI Business Law Review, 2025)
The implementation of the execution parate is regulated in Law Number 4 of 1996 concerning Mortgage Rights over land and objects related to the regulation of the execution model. In June 2023, the debtor borrowed credit from the creditor, namely BRI Rawamangun. For two years the debtor pays the credit smoothly, then in the third year the debtor is unable to pay off the credit. When providing credit, banks require collateral or collateral that can be used as a substitute for debt repayment if the debtor defaults. This research is normative legal research. The research approach uses a statutory approach, a case approach and a conceptual approach. The research stage uses library research, namely searching for secondary data using primary, secondary and tertiary legal materials. The legal material analysis technique uses qualitative analysis techniques. The results of the research show that, in setting the execution parate by the Bank for credit collateral objects due to default, the legal basis for the regulation of credit is Banking Law No. 10 of 1998 concerning credit agreements and Law No. 4 of 1996 concerning mortgage rights in article 6 related to the legal basis of the execution parate. This legal basis is the bank's power to carry out execution of credit guarantees due to default in good faith from the debtor who deliberately neglected to carry out the credit agreement.